2016
DOI: 10.1159/000453189
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of CDKN2A (p16INK4A/p14ARF) Over-Expression on Proliferation and Migration of Human Melanoma A375 Cells

Abstract: Objective: This study aims to investigate the effects of CDKN2A (p16INK4A/p14ARF) over-expression on the proliferation and migration of human melanoma A375 cells. Methods: Melanoma tissues and pigmented nevi tissues were collected. Human melanoma A375 cells were transfected by CDKN2A (p16INK4A) and CDKN2A (p14ARF) over-expressing vectors and then assigned into blank, negative control (NC), p16INK4A and p14ARF groups. The expression of CDKN2A (p1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…On the other hand, the highly proliferative Xiphophorus cell lines PSM and A2 exhibit only low expression of cdkn2ab mRNA and protein, whereas the slow proliferating SdSr24 cell line expresses cdkn2ab on a higher level. In vitro studies with mammalian cell lines revealed a clear inverse correlation between INK4A and/or ARF levels and proliferation (Bai et al., ) in agreement with the data from the fish cell lines. However, the expression levels of cdkn2ab determined from whole healthy organs or pigment lesion extracts are not reflecting the situation expected from the cell culture data, and thus do not provide a reliable read‐out for the proliferative state of a normal tissue or tumor.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…On the other hand, the highly proliferative Xiphophorus cell lines PSM and A2 exhibit only low expression of cdkn2ab mRNA and protein, whereas the slow proliferating SdSr24 cell line expresses cdkn2ab on a higher level. In vitro studies with mammalian cell lines revealed a clear inverse correlation between INK4A and/or ARF levels and proliferation (Bai et al., ) in agreement with the data from the fish cell lines. However, the expression levels of cdkn2ab determined from whole healthy organs or pigment lesion extracts are not reflecting the situation expected from the cell culture data, and thus do not provide a reliable read‐out for the proliferative state of a normal tissue or tumor.…”
Section: Discussionsupporting
confidence: 74%
“…While knockout of cdkn2ab promoted tumor progression, expression of a cdkn2ab transgene in pigment cells of the tg(mitfa:xmrk) melanoma medaka line resulted in a full suppression of tumor formation. Overexpression of p16/INK4A in A375 human melanoma cells inhibited proliferation and migration in vitro and led to decreased growth after xenotransplantation into nude mice (Bai, Yu, Long, Feng, & Wang, ). This is in agreement with our observation that cdkn2ab acts as a melanoma suppressor in fish.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, previous studies revealed the potential interactions between CDKN2A and PTEN genes and UVB radiation. CDKN2A may be involved in the proliferation and migration of melanoma cells, as the inhibitory effect was observed in CDKN2A -overexpressed melanoma A375 cells [ 43 ]. However, Krähn et al reported the inhibitory effect of UVB on CDKN2A expression in melanoma samples [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…P14ARF is one of the two proteins encoded by CDKN2A. It is involved in cell cycle regulation and senescence [ 51 ]. Its expression is decreased in melanoma compared with nevi tissues and is associated with stage, Clark grade and lymph node metastasis.…”
Section: Resultsmentioning
confidence: 99%